Intestinal parasite prevalence in an area of ethiopia after implementing the SAFE strategy, enhanced outreach services, and health extension program. - Jonathan D King; Tekola Endeshaw; Elisabeth Escher; Genetu Alemtaye; Sileabatt Melaku; Woyneshet Gelaye; Abebe Worku; Mitku Adugna; Berhanu Melak; Tesfaye Teferi; Mulat Zerihun; Demelash Gesese; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND: The SAFE strategy aims to reduce transmission of Chlamydia trachomatis through antibiotics, improved hygiene, and sanitation. We integrated assessment of intestinal parasites into large-scale trachoma impact surveys to determine whether documented environmental improvements promoted by a trachoma program had collateral impact on intestinal parasites. METHODOLOGY: We surveyed 99 communities for both trachoma and intestinal parasites (soil-transmitted helminths, Schistosoma mansoni, and intestinal protozoa) in South Gondar, Ethiopia. One child aged 2-15 years per household was randomly selected to provide a stool sample of which about 1 g was fixed in sodium acetate-acetic acid-formalin, concentrated with ether, and examined under a microscope by experienced laboratory technicians. PRINCIPAL FINDINGS: A total of 2,338 stool specimens were provided, processed, and linked to survey data from 2,657 randomly selected children (88% response). The zonal-level prevalence of Ascaris lumbricoides, hookworm, and Trichuris trichiura was 9.9% (95% confidence interval (CI) 7.2-12.7%), 9.7% (5.9-13.4%), and 2.6% (1.6-3.7%), respectively. The prevalence of S. mansoni was 2.9% (95% CI 0.2-5.5%) but infection was highly focal (range by community from 0-52.4%). The prevalence of any of these helminth infections was 24.2% (95% CI 17.6-30.9%) compared to 48.5% as found in a previous study in 1995 using the Kato-Katz technique. The pathogenic intestinal protozoa Giardia intestinalis and Entamoeba histolytica/E. dispar were found in 23.0% (95% CI 20.3-25.6%) and 11.1% (95% CI 8.9-13.2%) of the surveyed children, respectively. We found statistically significant increases in household latrine ownership, use of an improved water source, access to water, and face washing behavior over the past 7 years. CONCLUSIONS: Improvements in hygiene and sanitation promoted both by the SAFE strategy for trachoma and health extension program combined with preventive chemotherapy during enhanced outreach services are plausible explanations for the changing patterns of intestinal parasite prevalence. The extent of intestinal protozoa infections suggests poor water quality or unsanitary water collection and storage practices and warrants targeted intervention.